Microencapsulation techniques and encapsulating materials influenced the shelf life and digestion release of vitamin E and isoflavones in soymilk powder - Pakkawat Detchewa; Chutima Aphibanthammakit; Anuchita Moongngarm; Sylvie Avallone; Patcharee Prasajak; Chadaporn Boonpan; Varathip Ruangdath; Wichien Sriwichai (Scientific Reports)
Abstract Soymilk, due to its high-quality protein and isoflavones content, is widely consumed worldwide. Unfortunately, soymilk lacks the powerful antioxidant vitamin E. Encapsulation of vitamin E and isoflavones in soymilk powder is advantageous for malnourished consumers to meet the recommendation. This study aimed to evaluate the impact of different encapsulation techniques and encapsulating materials on the storage stability and bioaccessibility of vitamin E and isoflavones in soymilk powder. Freeze-drying and spray-drying methods were applied with various encapsulating materials prepared from different ratios of maltodextrin to Acacia gum (100:0, 60:40, 50:50, 40:60, and 0:100). The results indicated that a 40:60 ratio of maltodextrin and Acacia gum provided the highest stability for 24 h of soymilk emulsion under the studied conditions. The shelf-life prediction of soymilk powder increased by more than two weeks when stored at 0 °C compared to the storage at ambient temperature. Spray-drying and freeze-drying techniques effectively encapsulate vitamin E and isoflavones within core microcapsules. Especially, freeze-drying process helps to prevent degradation during storage and allows for controlled release of the bioactive compounds during in-vitro digestion. Encapsulation efficiency of isoflavones and vitamin E for all formulation ranged from 80.9 ± 0.01% to 83.5 ± 0.20%, respectively. The highest vitamin E and isoflavones bioaccessibility of encapsulated product increased by up to 4.4-fold and 1.7-fold in the 60:40 formulations. Consuming 20 g of encapsulated vitamin E and 170 g of encapsulated isoflavones daily would be sufficient to meet the recommended intake.